Early virologic response to сеpeginterferon alfa-2b in combination with ribavirin in treatment of patients with chronic hepatitis C - O. O. Znoyko; M. V. Maevskaya; E. A. Klimova; S. L. Maksimov; S. N. Kizhlo; N. A. Petrochenkova; F. I. Nagimova; R. A. Ivanov; Yu. N. Linkova; T. V. Chernovskaya (Журнал инфектологии)
Algeron (cepeginterferon alfa-2b) is a new pegylated form of interferon alfa containing linear polyethylene glycol (molecular weight 20 kDa). Pharmacokinetic profile of Algeron allows once weekly administration. In phase II–III study 150 treatment-naive patients with compensated liver function were randomized into 3 groups: Algeron 1,5 μg/kg/week, Algeron 2,0 μg/kg/week, and a reference group of PegIntron 1.5 μg/kg/week in combination with ribavirin 800– 1400 mg/day. Comparative ITT -analysis of early virologic response (EVR) showed absence of differences between groups in frequency of EVR. In Algeron groups (regardless of a dose – 1,5 or 2,0 μg/kg) EVR was observed in 94%, in PegIntron group – – in 88% of patients. Complete EVR (HCV RNA≤15 I I U/mL) was recorded in 88% and 84% of patients receiving Algeron 1,5 and 2,0 μg/kg, respectively, in the reference group – – in 84% of patients. There were no statistically significant differences between groups where patients received Algeron in different doses and the reference group, with or without genotype stratification. Adverse events occurring during the treatment with Algeron are dose-dependent; however, their frequency is no more than in patients receiving standard doses of PegIntron. Based on the absence of differences in efficacy and more favorable safety profile of a lower dose of the study drug, the therapeutic dose of Algeron was selected to be 1,5 μg/kg/week.